A REVIEW ON BIOACTIVE PHYTOCHEMICALS AND IT’S MECHANISM ON CANCER TREATMENT AND PREVENTION BY TARGETING MULTIPLE CELLULAR SIGNALING PATHWAYS - BHUTADIYA, VARSHA L.; MISTRY, KINNARI N. (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
In developing and developed countries, cancer is a significant health problem in people. Cancer becomes the second greatest cause of death in human after cardiovascular disease. However, significant advancements in modern cancer therapies have a beneficial impact on survival, chemotherapy and radiation therapy. Plants fulfill our basic needs to continue life and provide natural products that help to cure disease. The medicinal plants are readily available and have no toxicity as compared to modern drugs. Phytochemicals act on metabolic pathways and inhibit tumor growth, the development of cancerous cells, and replication by different mechanisms. Apigenin's chemo-preventive and anticancer activities have been demonstrating in numerous studies. Curcumin is a polyphenolic compound isolated from the Curcuma longa plant. EGCG, a polyphenol in black, white, and green tea is a chemo-preventive effect against many cancers by targeting multiple pathways. Normal cell growth and cell proliferation are closely regulated processes. The JAK-STAT (Janus kinase-signal transducer and activator of transcription) pathway controls gene expression during different processes, including proliferation, initiation, and apoptosis. The transcription factors are associated with the growth of cancer cells and control a cellular function in the disease. Mitogen-activated protein kinase (MAPK) is a class of serine and threonine kinase that includes ERK (extracellular regulated kinase), JNK (c-Jun N-terminal kinases), and p38. This review paper describes natural phytochemical compounds, their molecular targets and mechanisms of action.